Comparative Study of Bi-Te-Se-S Mineralizations in Slovak Republic and Transcarpathian Region of Ukraine. Part 1. Localities, Geological Situation and Mineral Associations - Melnikov, V.; Jelen, S.; Bondarenko, S.; Balintova, T.; Ozdin, D.; Grinchenko, A. (Мінералогічний журнал, 2009)
Comparative analysis of telluride occurrences found in the territory of Slovakia and Transcarpathians (Ukraine) has shown that there is distinct difference between the mode of Au-Ag-Bi-Te-Se mineralization of these regions. But within the area of distribution of neovolcanites Bi-Te-Se-S mineralization is generally represented by similar mineralogical phases. In the Transcarpathian region bismuth tellurides (tsumoite, pilsenite, joseites, native bismuth and poorly studied sulpho-selenotellurides of bismuth) were found only in metasomatites as secondary quartzites of the Vyghorlat-Guta ridge area. (Il'kivtsy, Podulky, Smerekiv Kamin'). The similar mineralization have been also found in some neovolcanites of Slovakia (Poruba pod Vigorlatom, Remetska Hamra). Порівняльний аналіз проявів телуридів на території Словаччини і Закарпаття (Україна) показав, що існує помітна відмінність в характері Au-Ag-Bi-Te-Se мінералізації цих регіонів. Але в областях розвитку неовулканітів Bi-Te-Se-S мінералізація представлена в основному аналогічними мінеральними фазами. Телуриди вісмуту (цумоїт, пильзеніт, жозеїти, самородний бісмут і маловивчені сульфо-селено-телуриди бісмуту) знайдені на території Закарпаття тільки в метасоматитах типу вторинних кварцитів Вигорлат-Гутинського пасма (Ільківці, Подулки, Смереків Камінь). Подібна мінералізація встановлена в деяких неовулканітах Словаччини (Poruba роd Vigorlatom, Remetska Hamra). Сравнительный анализ проявлений теллуридов на территории Словакии и Закарпатья (Украина) показал, что существует заметное различие в характере Au-Ag-Bi-Te-Se минерализации этих регионов. Но в областях развития неовулканитов Bi-Te-Se-S минерализация представлена в основном аналогичными минеральными фазами. Теллуриды висмута (цумоит, пильзенит, жозеиты, самородный висмут и малоизученные сульфо-селенотеллуриды висмута) найдены на территории Закарпатья только в метасоматитах типа вторичных кварцитов Выгорлат-Гутинской гряды (Ильковцы, Подулки, Смерекив Каминь). Подобная минерализация установлена в некоторых неовулканитах Словакии (Poruba pod Vigorlatom, Remetska Hamra).